Oepke Noordmans en Paul Scholten - Balke, Willem (Hervormde teologiese studies, 1992)
Oepke Noordmans and Paul Scholten Two prominent figures of this century, Paul Scholten, one of the most outstanding professors of law of his time, and the genial theologian, Oepke Noordmans, corresponded over a long period of time. Scholten was a lawyer with a profound interest in theology, while Noordmans was involved in laying the foundations of church order. Their correspondence affords a special insight into their views on the developments around them in which they themselves played a leading role.